2008
DOI: 10.1080/14992020802331222
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular failure in children with congenital deafness

Abstract: Congenitally deaf infants and children commonly suffer vestibular failure in both ears, and impairment of postural control, locomotion, and gait. The development of gross motor functions, such as head control, sitting, and walking is likely to be delayed, but fine motor function is usually preserved unless disorders of the central nervous system are present. These children can eventually catch up with their normal peers in terms of development and growth as a result of central vestibular compensation. The visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
41
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 10 publications
5
41
1
4
Order By: Relevance
“…Therefore, children with profound sensorineural hearing loss may also exhibit peripheral vestibular impairments [Shinjo et al, 2007;Cushing et al, 2008a;Kaga et al, 2008;Jacot et al, 2009]. It has been reported that children with profound hearing loss tend to display balance dysfunction and delayed acquisition of gross motor skills, such as head control, sitting and walking, compared with children with normal hearing [Potter and Silverman, 1984;Butterfield, 1986;Crowe and Horak, 1988;Suarez et al, 2007;Cushing et al, 2008a].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, children with profound sensorineural hearing loss may also exhibit peripheral vestibular impairments [Shinjo et al, 2007;Cushing et al, 2008a;Kaga et al, 2008;Jacot et al, 2009]. It has been reported that children with profound hearing loss tend to display balance dysfunction and delayed acquisition of gross motor skills, such as head control, sitting and walking, compared with children with normal hearing [Potter and Silverman, 1984;Butterfield, 1986;Crowe and Horak, 1988;Suarez et al, 2007;Cushing et al, 2008a].…”
Section: Introductionmentioning
confidence: 99%
“…As they grow older, they progressively begin to use somatosensory and vestibular information until these systems reach full maturity around the age of 10 years [Kaga, 1999;Wallacott et al, 2004;Suarez et al, 2007]. Since vestibular function plays an important role in the development of balance and locomotion, impairment of the vestibulospinal system in infancy may lead to delayed achievement of gross motor milestones [Eviatar et al, 1979;Kaga, 1999;Kaga et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Uma vez que o sistema vestibular e a cóclea são órgãos anatomicamente muito próximos e podem ser suscetíveis aos mesmos agentes nocivos, é razoável presumir que crianças surdas podem apresentar problemas vestibulares, concomitantes, à perda auditiva sensorioneural [7][8][9] . Além disso, estudos têm relatado que a hipoatividade do sistema vestibular tem sido citada como um achado frequente em avaliações otoneurológicas de crianças com perda auditiva sensorioneural, o que poderia causar nestas crianças distúrbios vestibulares 10,11 . Os distúrbios vestibulares na infância não são tão raros como se supõe, podem afetar a aquisição de habilidades motoras ou interferir, principalmente, na integração sensorial do sistema vestibular desta população.…”
Section: Introductionunclassified
“…Por meio de programas de treinamento baseado em exercícios que envolvam o equilíbrio corporal (Exemplo: jogos com bola, trampolim acrobático, dança, entre outros), os surdos podem desenvolver estratégias posturais para superar ou compensar as eventuais dificuldades de equilíbrio 21 . Estas estratégias posturais são decorrentes da neuroplasticidade, a qual determina que as funções do sistema vestibular afetado possam ser compensadas por outros sentidos, atingindo-se um desenvolvimento semelhante aos dos sujeitos sem alterações no equilíbrio 4,7,14 . É a teoria da compensação 17,22 .…”
Section: Introductionunclassified
“…Conclusão: a análise dos resultados apontou para um desempenho melhor das crianças ouvintes, em relação às surdas, no que se refere ao equilíbrio estático, dinâmico e recuperado. Uma vez que o aparelho vestibular e a cóclea são órgãos anatomicamente muito próximos e devem ser susceptíveis aos mesmos agentes nocivos [7][8][9][10]14 , é razoável presumir que muitas crianças surdas têm problemas vestibulares concomitantes à perda auditiva. A hipoatividade vestibular é citada como achado frequente em crianças com perda auditiva severa 15 .…”
unclassified